Current Advancements in Spinal Cord Injury Research—Glial Scar Formation and Neural Regeneration - Tanner Clifford; Zachary Finkel; Brianna Rodriguez; Adelina Joseph; Li Cai (Cells, 2023)
Spinal cord injury (SCI) is a complex tissue injury resulting in permanent and degenerating damage to the central nervous system (CNS). Detrimental cellular processes occur after SCI, including axonal degeneration, neuronal loss, neuroinflammation, reactive gliosis, and scar formation. The glial scar border forms to segregate the neural lesion and isolate spreading inflammation, reactive oxygen species, and excitotoxicity at the injury epicenter to preserve surrounding healthy tissue. The scar border is a physicochemical barrier composed of elongated astrocytes, fibroblasts, and microglia secreting chondroitin sulfate proteoglycans, collogen, and the dense extra-cellular matrix. While this physiological response preserves viable neural tissue, it is also detrimental to regeneration. To overcome negative outcomes associated with scar formation, therapeutic strategies have been developed: the prevention of scar formation, the resolution of the developed scar, cell transplantation into the lesion, and endogenous cell reprogramming. This review focuses on cellular/molecular aspects of glial scar formation, and discusses advantages and disadvantages of strategies to promote regeneration after SCI.